Pengaruh Pengetahuan Pajak Terhadap Motivasi Dan Dampaknya Terhadap Minat Berkarir Mahasiswa Di Bidang Pajak (Studi Kasus Pada Mahasiswa Program Studi Akuntansi Perpajakan Program Sarjana Terapan Universitas Pamulang) - Siti Asmonah; Siti Ratna Sari Dewi; Danang Choirul Umam (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of tax knowledge on motivation (both internal and external) and its impact on students’ interest in pursuing a career in taxation. The research subjects were seventh- and eighth-semester students of the Applied Bachelor Program in Tax Accounting at Pamulang University who had completed taxation courses. A total of 90 respondents were selected using purposive sampling with specific criteria. This study employed a quantitative approach, and data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through SmartPLS 3.0 software. The results indicate that tax knowledge does not directly influence career interest but has a significant effect on both internal and external motivation. Furthermore, external motivation significantly influences career interest, whereas internal motivation does not. Mediation analysis reveals that external motivation significantly mediates the relationship between tax knowledge and career interest, while internal motivation does not show a meaningful mediating effect. These findings highlight the importance of external support in bridging the influence of tax knowledge on students’ tendencies to pursue careers in the taxation field.